Funkcjonowanie świetlic socjoterapeutycznych w czasie pandemii COVID-19 w Gdańsku, Poznaniu i Katowicach - Brzezińska , Adrianna; Jankowiak , Barbara; Soroko , Emilia (Studia Edukacyjne, 2023)
Socio-therapeutic day-care facilities are specifically dedicated to the conduct of socio-therapeutic activities for children and adolescents from high-risk groups and those displaying difficulties in psycho-social functioning. During the pandemic, socio-therapeutic day facilities continued to aid their clients. The aim of this analysis is to describe the operation of socio-therapeutic day care facilities in Gdańsk, Katowice and Poznań. The data collection method for this project is a semi-structured telephone interview, while data is examined via a template analysis. The analyses concerned 30 socio-therapeutic day care facilities in Gdańsk, Katowice and Poznań. The data collected shows that socio-therapeutic day facilities could be an important source of support for the participants and their families. Elements of socio-therapeutic work were retained in contact with the clients to the highest possible degree via online communication. Online meetings enabled discussion of current difficulties, emotional respite and support. Topics discussed included those supporting health-promoting behavior in an epidemiological emergency. Many of the activities went beyond group work and were mainly supportive or crisis intervention. Staff members contacted parents, helped with children’s homework and even donated food parcels.